2022
DOI: 10.3390/ijms23073479
|View full text |Cite
|
Sign up to set email alerts
|

A New Target of Dental Pulp-Derived Stem Cell-Based Therapy on Recipient Bone Marrow Niche in Systemic Lupus Erythematosus

Abstract: Recent advances in mesenchymal stem/stromal cell (MSC) research have led us to consider the feasibility of MSC-based therapy for various diseases. Human dental pulp-derived MSCs (hDPSCs) have been identified in the dental pulp tissue of deciduous and permanent teeth, and they exhibit properties with self-renewal and in vitro multipotency. Interestingly, hDPSCs exhibit superior immunosuppressive functions toward immune cells, especially T lymphocytes, both in vitro and in vivo. Recently, hDPSCs have been shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…MSCs exhibit an immunomodulatory property to a variety of immune cells, such as T lymphocytes, B lymphocytes, and macrophages ( 45 , 46 ). The immunosuppressive functions of MSCs are explained by the following three mechanisms: 1) indirect intercellular communications with innate and adaptive immune cells by paracrine factors, including growth factors, cytokines, and container within EVs, such as miRNA; 2) direct intercellular communications with T lymphocytes through cell surface molecules, such as FasL and program death ligand 1; 3) efferocytosis of T lymphocyte-induced ApBs of MSCs, followed by secreting immunosuppressive factors from phagocytes ( 23 , 47 ).…”
Section: A Novel Mechanism Of Msc-ev Therapy Through Microenvironment...mentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs exhibit an immunomodulatory property to a variety of immune cells, such as T lymphocytes, B lymphocytes, and macrophages ( 45 , 46 ). The immunosuppressive functions of MSCs are explained by the following three mechanisms: 1) indirect intercellular communications with innate and adaptive immune cells by paracrine factors, including growth factors, cytokines, and container within EVs, such as miRNA; 2) direct intercellular communications with T lymphocytes through cell surface molecules, such as FasL and program death ligand 1; 3) efferocytosis of T lymphocyte-induced ApBs of MSCs, followed by secreting immunosuppressive factors from phagocytes ( 23 , 47 ).…”
Section: A Novel Mechanism Of Msc-ev Therapy Through Microenvironment...mentioning
confidence: 99%
“…In the following literature, we discuss a unique mechanism of action of SHED-EV therapy for osteopenia treatment, which rejuvenate the bone marrow microenvironment through recipient BMMSCs ( 40 , 47 , 92 ).…”
Section: A Novel Mechanism Of Msc-ev Therapy Through Microenvironment...mentioning
confidence: 99%
See 1 more Smart Citation
“…hDPSCs have shown higher growth potential than human bone marrow-derived stem cells (hBMSCs). Meanwhile, hDPSCs have been shown to have potent immunomodulatory functions in treating systemic lupus erythematosus (SLE) in the SLE MRL/lpr mouse model ( 6 ). Yan et al also indicated that hDPSCs could inhibit the progression of fibrosis in hypertrophic keloids ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hDPSC can release soluble immunosuppressive molecules such as prostaglandin E2 (PGE2), transforming growth factor β (TGF-β), and nitric oxide (NO) in a paracrine manner to suppress the T cell inflammatory response [ 18 ]. Studies have reported that hDPSC is able to treat a variety of autoimmune and inflammation-related diseases in vivo and vitro [ 19 , 20 ]. However, studies on the treatment of psoriasis by hDPSC have not been reported.…”
Section: Introductionmentioning
confidence: 99%